Design and Simulation of Ultrasonic Triangular Blades for Honeycomb Structures Cutting - Vjuginova, Alena A.; Durukan, Yasemin; Vjuginov, Sergey N.; Novik, Alexander A. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2021)
Honeycomb materials, composite and aluminum, are widely used in aerospace, automotive and other fields due to their outstanding characteristics such as high strength, rigidity, low density and good thermal insulation properties. At the same time, the processing of honeycomb materials is associated with a number of difficulties, and one of the technologies that allows effectively solving the layout problems for honeycomb materials is ultrasonic cutting. In this work triangular blades for ultrasonic cutting of honeycomb materials with operating frequency 20 kHz with different geometric parameters for different variants of honeycomb structures are analyzed. Eigenfrequency properties are studied for ultrasonic triangular blade's shape and length and experimental results for a number of deigns are presented.